ROLE OF REPEAT CT SCAN BRAIN FOR PATIENTS WITH HEAD TRAUMA WHO ARE BEING MANAGED CONSERVATIVELY - Dr Ali Raza; Professor Dr Lal Rehman; Dr Mujahid Shareef; Dr Naveed Ahmed; Dr Naveed khan; Dr Muhammad Najeeb; Dr Mashal Rasool (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Traumatic Brain Injury (TBI) can result from a number of factors such as a simple blow to the head or it can be a result of sever penetrating trauma to skull.Objective: To find out the efficacy of repeat CT scan in guiding management of patient with mild traumatic brain injury.Material and methods: This Prospective observational study was conducted at Department of Neurosurgery, Pakistan Institute of Medical Sciences, Islamabad during July 2023 to June 2024. Patients presenting to the ER department were enrolled in the study and managed according to ATLS guidelines. Those with mild traumatic brain injury were managed conservatively if the initial CT scan did not indicate the need for urgent surgical intervention. Patients managed conservatively underwent a repeat CT scan at a 4–6-hour interval or sooner if their clinical condition deteriorated.Results: Data were collected from 227 patients according to criteria of the study. Mean age of the patients was 35.4 ± 10.2 years, of whom 154 (68%) were male and 73 (32%) were female. The mean Glasgow Coma Scale (GCS) score was 14.2 ± 1.1, indicating that most patients had mild head trauma. Vital signs at presentation showed an average blood pressure of 125/80± 15/10 mmHg and a mean heart rate of 78 ± 12 bpm. The most common mechanism of injury was road traffic accidents, accounting for 50% of cases, followed by falls (30%), assaults (12%), sports-related injuries (5%), and other causes (3%).Conclusion: It is concluded that repeat CT scanning is essential for the effective management of patients with head trauma who are being managed conservatively. The repeat imaging significantly contributes to detecting changes in intracranial pathology, which can lead to timely surgical intervention and improved patient outcomes